2022
DOI: 10.3823/862
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D treatment on COVID 19- Patients, an Inverted Propensity Score Weighting (IPSW), and Inverted Probability of Treatment Weighting (IPTW) Analyzed Study

Abstract: Background Vitamin D3 (1,25(OH)2 cholecalciferol) as a treatment for COVID 19 patients is being disputed, and a clear clinical benefit is not being confirmed. Methods A retrospective evaluation for COVID-19 patients who were treated with various cumulative doses of vitamin D. Data was extracted from the COVID-19 database, it included patients admitted to three hospitals in Amman, Jordan. Characteristics of patients were tabulated and compared for all-cohort, and propensity score index (PSI) adjustment, The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Also, a time frame for initiating steroids was cited, i.e., to use steroids if symptoms were >7 days, or the patient was hospitalized >72 hours off invasive mechanical ventilation [10]. Nonetheless, a Cochrane review on steroid treatment in patients with severe COVID-19 disease concluded that "Systemic corticosteroids plus standard care compared to standard care probably reduce the 30 days all-cause mortality (low to moderate-certainty evidence) slightly" [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a time frame for initiating steroids was cited, i.e., to use steroids if symptoms were >7 days, or the patient was hospitalized >72 hours off invasive mechanical ventilation [10]. Nonetheless, a Cochrane review on steroid treatment in patients with severe COVID-19 disease concluded that "Systemic corticosteroids plus standard care compared to standard care probably reduce the 30 days all-cause mortality (low to moderate-certainty evidence) slightly" [11].…”
Section: Introductionmentioning
confidence: 99%